IoT Enabled Real Time Load Height Monitoring and Control System Using PLC and HMI for Smart Industrial - Hendrawati, Dwiana; Hakim, Ermanu Azizul; Dionova, Brainvendra Widi; Sulistyo, Ahmad Kholik; Abdullah, Muhammad Irsyad (Journal of Applied Engineering and Technological Science (JAETS), 2025)
This study develops a laboratory-scale prototype of an IoT-enabled, real-time load height monitoring and control system that integrates Programmable Logic Controllers (PLCs), Human–Machine Interfaces (HMIs), and cloud-based MQTT communication. Developed and validated under controlled conditions, the prototype consistently demonstrates sub-2-second latency (0.66–1.58 seconds) across varying network speeds, confirming its technical feasibility for future industrial applications. Proximity sensors and PLCs enable precise load height measurement, while the Haiwell C7S HMI provides real-time visualization and multi-platform control via web and mobile interfaces. Experimental results highlight the prototype’s robustness, scalability, and alignment with Industry 4.0 frameworks, offering a foundational architecture for subsequent industrial deployment. This work bridges the gap between theoretical Cyber-Physical Systems (CPS) principles and practical implementation, emphasizing adaptability and low-latency performance for smart manufacturing ecosystems.